Pengaruh Service Excellence dan Handling Complaint Terhadap Kepuasan Pemustaka Pascasarjana Universitas Muhammadiyah Sumatera Utara (UMSU) - Maretta Ginting; Ronnie Togar Mulia Sirait; Hilda Syaf'aini Harefa (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2023)
This study aims to identify and analyze service excellence which has a positive and significant partial effect on user satisfaction, to determine and analyze complaint handling which has a positive and significant partial effect on user satisfaction and to determine and analyze service excellence and complaint handling which have a positive and significant effect simultaneously. on user satisfaction at the Postgraduate Library of Muhammadiyah University of North Sumatra (UMSU). The type of research used is descriptive quantitative. The population in this study was 1,419 members of the Postgraduate Library. The sample in the study was 93 respondents using the Simple Random Sampling technique. The analytical method used is instrument test, classical assumption test, hypothesis test, coefficient of determination test and multiple linear regression analysis. The results showed (1) Based on the Partial Test (t test) service excellence has a positive and significant effect on user satisfaction at the Postgraduate Library of Muhammadiyah University of North Sumatra (UMSU), (2) complaint handling has a positive and significant effect on user satisfaction at the Postgraduate Library of Muhammadiyah University North Sumatra (UMSU), (3) Based on the Simultaneous Test (F Test) service excellence and complaint handling simultaneously have a positive and significant effect on user satisfaction at the Postgraduate Library of Muhammadiyah University of North Sumatra (UMSU).